Muscles susceptibility to ischemia-reperfusion injuries depends on fiber type specific antioxidant level - CHARLES, Anne-Laure; Guilbert, Anne-Sophie; Guillot, Max; Talha, Samy; Lejay, Anne; Meyer, Alain; Kindo, Michel; wolff, valerie; Bouitbir, Jamal; Zoll, Joffrey; GENY, Bernard (Frontiers in Physiology, 2017)
Muscle injury resulting from ischemia-reperfusion largely aggravates patient prognosis but whether and how muscle phenotype modulates ischemia-reperfusion-induced mitochondrial dysfunction remains to be investigated. We challenged the hypothesis that glycolytic muscles are more prone to ischemia-reperfusion-induced injury than oxidative skeletal muscles. We therefore determined simultaneously the effect of 3 hours of ischemia induced by aortic clamping followed by 2 hours of reperfusion (IR, n=11) on both gastrocnemius and soleus muscles, as compared to control animals (C, n=11). Further, we investigated whether tempol, an antioxidant mimicking superoxide dismutase, might compensate a reduced defense system, likely characterizing glycolytic muscles (IR-Tempol, n=7). In the glycolytic gastrocnemius muscle, as compared to control, ischemia-reperfusion significantly decreased mitochondrial respiration (-30.28 ± 6.16 %, p =0.003), increased reactive oxygen species production (+79.15 ± 28.72 %, p =0.04), and decreased reduced glutathione (-28.19 ± 6.80%, p =0.011). Less deleterious effects were observed in the oxidative soleus muscle (-6.44 ± 6.30%, +4.32 ± 16.84%, and -8.07 ± 10.84%, respectively), characterized by enhanced antioxidant defenses (0.63 ± 0.05 in gastrocnemius vs. 1.24 ± 0.08 µmol L-1 g-1 in soleus). Further, when previously treated with tempol, glycolytic muscle was largely protected against the deleterious effects of ischemia-reperfusion. Thus, oxidative skeletal muscles are more protected than glycolytic ones against ischemia-reperfusion, thanks to their antioxidant pool. Such pivotal data support that susceptibility to ischemia-reperfusion-induced injury differs between organs, depending on their metabolic phenotypes. This suggests a need to adapt therapeutic strategies to the specific antioxidant power of the target organ to be protected.